Precariat as a phenomenon of the modern labour market in Poland and in the European Union - Knapińska, Magdalena (Archives of Business Research, 2019)
The aim of the article is to define precariat, a new notion, which describes the status of some social groups on the labour market. An attempt has been made to identify determinants of this phenomenon as well as its characteristic features, which justify eliciting this group on the labour market. In the first part of the article the notion of precariat is defined according to the subject literature. In the second part its economic features and range scale in Poland have been discussed, followed by the third part focusing on the EU labour market. Finally, in the fourth part, the occurrence of the phenomenon of precariat on the modern labour market has been evaluated. Final conclusions stemming from the analysis have been enclosed in the final part of the article.